2021
DOI: 10.17061/phrp3112104
|View full text |Cite
|
Sign up to set email alerts
|

Impact of funding on influenza vaccine uptake in Australian children

Abstract: In 2018, most Australian jurisdictions introduced free influenza vaccines for children younger than 5 years • Self-reported vaccination rates for young children increased by 2.7-4.2-fold in jurisdictions with policies introducing funded vaccines in 2018 • Flow-on effects occurred in children aged 5-17 years, with vaccination rates increasing by 1.2-2.2-fold in this unfunded population • Our results highlight the importance of funding in increasing the uptake of seasonal influenza vaccines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Dyda et al performed a systematic review on influenza and pneumococcal vaccination rates in Australian adults from 1990 to 2015, which revealed the coverage of both vaccines was significantly higher following the introduction of universal funding (for influenza, pre and post-funding, 61.3% vs 74.8%, p<0.001) [ 27 ]. Howard et al also reported large increases in vaccination rates for children <5 years in 2018 that coincided with the introduction of funded vaccines in Australia (OR 4.75, 95% CI 4.57–4.79) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dyda et al performed a systematic review on influenza and pneumococcal vaccination rates in Australian adults from 1990 to 2015, which revealed the coverage of both vaccines was significantly higher following the introduction of universal funding (for influenza, pre and post-funding, 61.3% vs 74.8%, p<0.001) [ 27 ]. Howard et al also reported large increases in vaccination rates for children <5 years in 2018 that coincided with the introduction of funded vaccines in Australia (OR 4.75, 95% CI 4.57–4.79) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…We allowed the nurses to use additional distraction techniques in the intervention protocols for ethical reasons—this is considered best‐practice care (Birnie et al, 2018) and thus, we recommend future studies do the same and seek to determine the effects of the new interventions in addition to best‐practice care. Secondly, recruitment rates were low, likely due to the absence of government‐funded influenza vaccines for children aged 8–12, a feature shown to influence vaccine uptake (Howard et al, 2021). Thus, future studies should consider another type of injection that is typically scheduled (e.g., measles/mumps/rubella) rather than an entirely voluntary vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Howard et al assessed the impact of funded influenza vaccine programmes in Australia by comparing vaccine uptake before and after the introduction of funded vaccines for children aged 6 months to less than 5 years and showed that government-funded vaccines can lead to an almost fivefold increase in vaccine uptake in the target age group. They also found that funded vaccines for young children may encourage caregivers to also vaccinate themselves and their older children [ 18 ]. Most importantly, De Oliveira Bernard et al highlighted that the patients attending practices in the most affluent areas had the highest vaccination coverage in all years and they benefited most from this Australian government-funded influenza programme [ 19 ].…”
Section: Discussionmentioning
confidence: 99%